Different cell compositions and a novel somatic KCNJ5 variant found in a patient with bilateral adrenocortical adenomas secreting aldosterone and cortisol - Zhao, Liling; Wan, Jinjing; Wang, Yujun; Yang, Wenjun; Liang, Qi; Wang, Jinrong; Jin, Ping (Frontiers in Endocrinology, 2023)
Introduction: The aim of this study was to explore the possible pathogenesis of a rare case of co-existing Cushing’s syndrome (CS) and primary aldosteronism (PA) caused by bilateral adrenocortical adenomas that secreted aldosterone and cortisol, respectively. Methods: A 41-year-old Chinese woman with severe hypertension for five years and hypokalemia for two years was referred to our hospital. She had a Cushingoid appearance. Preoperative endocrinological examinations revealed autonomous cortisol and aldosterone secretion. A computerized tomographic scan revealed bilateral adrenal adenomas. Subsequently, adrenal vein sampling and sequential left and right partial adrenalectomy indicated the presence of a left aldosterone-producing tumor and a right cortisol-producing tumor. Pathological examination included immunohistochemical analysis of the resected specimens. Secretion of aldosterone and cortisol were observed both in vivo and in vitro. Whole-exome sequencing was performed on DNA that was extracted from peripheral blood leukocytes and bilateral adrenal adenomas to determine whether the patient had relevant variants associated with PA and CS. Results: Immunohistochemical staining revealed the left adenoma consisted primarily of clear cells with CYP11B2 expression, while the right adenoma was composed of both eosinophilic compact and clear cells with CYP11B1 expression. The mRNA levels of steroidogenic enzymes, including CYP11B1 and CYP17A1, were high in the right adenoma, while CYP11B2 was highly expressed in the left adenoma. A novel somatic heterozygous missense variant KCNJ5 c.503T > G (p.L168R) was detected in the left adrenal adenoma, but no other causative variants associated with PA and CS were observed in peripheral blood samples or the right adrenocortical adenoma. In the primary cell culture of the resected hyperplastic adrenal adenomas, verapamil and nifedipine, two calcium channel blockers, markedly inhibited the secretion of both aldosterone and cortisol. Conclusion: In conclusion, we analyzed an extremely rare case of bilateral adrenocortical adenomas with distinct secretion of aldosterone and cortisol. The heterogeneity of aldosterone- and cortisol-producing adenoma (A/CPA) tumor cell compositions and the KCNJ5 somatic mutation may be the reasons behind different hormone secretions in the bilateral adrenal adenomas.